2001
DOI: 10.1080/01443410120090830
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Factors Influencing the Academic Self-concept, Self-esteem and Academic Stress for Direct and Re-entry Students in Higher Education

Abstract: Establishments of Higher Education (HE) are generally recruiting a more diverse student population. This research has speci cally examined differences in the undergraduate student experience of direct and re-entry students. One hundred and twelve undergraduate direct and re-entry students took part in the study. A six-part questionnaire was used to investigate the impact of age, gender, past experiences of school and motivations for participating in HE on current global self-esteem, academic self-concept and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 26 publications
(41 reference statements)
2
77
0
8
Order By: Relevance
“…Michie et al (2001) found that women are more likely to report larger amounts of academic stress than men, and also that women often have less confidence in their educational abilities than men. Gender differences have also been found in the effect of social comparison on academic confidence.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Michie et al (2001) found that women are more likely to report larger amounts of academic stress than men, and also that women often have less confidence in their educational abilities than men. Gender differences have also been found in the effect of social comparison on academic confidence.…”
Section: Gender Differencesmentioning
confidence: 99%
“…For instance, students may experience the sense of being under psychological pressure [3,6,7], with academic stress affecting self-concept [8] and self-esteem [2,8]. Although stress may not affect all university students, research shows that an arguably significant number of students report experiencing stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are not always addressing the needs of all ''different'' types of students. 5 More students are attending college as re-entry students, those who are over the age of 22, and with a gap in their education. Such students are particularly prone to a lack of confidence as learners and underestimate their own ability, but often counter this with a higher degree of motivation for learning.…”
Section: Introductionmentioning
confidence: 99%
“…Re-entry students appear to have special needs that must be addressed for them to make the transition from ''citizenin-the-world'' to student. 5 The most significant indicators of educational stress are a reduction in academic performance, 6,7 increased alcohol consumption, smoking, and an increased tendency to think about suicide. 8 Spegman and Herrin found chiropractic student's depression and stress rates to be similar to the general population (25%-30%), but that the students had a diverse range of strategies for coping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation